PERSISTENSI TOKSISITAS BIOINSEKTISIDA SPHEREFIXTM PADA BEBERAPA TIPE TEMPAT PERINDUKAN NYAMUK Aedesaegypti L. - Salamun Salamun; S A Husein; Rosmanida Rosmanida; Dwi Winarni; Tri Nurhariyati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
SpherefixTM bioinsecticide is microbial agent of Bacillus sphaericus H-5a5b (VCRC B24) showing high potency for vector control. The bioinsecticide specific to target insect, and do not produce any adverse environmental impact, so the bioinsecticide would be very promising agent for vector control, especially vector of dengue haemorrhagic fever in Indonesia. The present studies aimed at observing the toxicity persistence of SpherefixTM on the larvae Aedesaegypti L. in some types of water container, and recycling potencies in the breeding places of A.aegypti. Two steps of the studies were carried out under laboratory conditions. Firststeps were reared mosquitos in the laboratory to supply larvae of Aedes aegypti. Second step testing of SpherefixTM toxicity persistence in the cemented, clay, and plastic containiers. The bioinsecticides were preparated by Vector Control Research Centre (VCRC), India. The toxicity persistence of SpherefixTM on the larvae of A. aegypti L. in some types of water container were decided by probit analysis. The toxicity persistence tests were carried out by time series observation on the day 1, 6, 12,,,, and 120. The result showed that difference toxicity persistence of the SpherefixTM in the breeding places of A. aegypti. The cemented container was found to have longest of toxicity persistence of the SpherefixTM followed by the plastic container, and the clay container ha the shortest duration toxicity persistence. The higher concentration of the boinsecticides, will result in higher toxicity persistence. The SpherefixTM showed recycling potency in the breeding places of A. aegypti. Percent motility of the larvae dropped sharply after day 50, and larvae mortality under 5% after day 78.